Topical sirolimus for the treatment of facial angiofibromas in tuberous sclerosis patient: a case report - Bhardwaj, Ankit; Manjhi, Mukesh (International Journal of Research in Dermatology, 2022)
Tuberous sclerosis complex (TSC) is an autosomal-dominant neurocutaneous disorder seen in 1/6000 births. Facial angiofibroma is the most common cosmetic disfiguring cutaneous manifestation of it. Therapeutic modalities include cryotherapy, podophyllotoxin application, electrocoagulation, surgery and laser therapy associated with their own high risk of complications and sequelae. Sirolimus is a lipophilic lactone isolated from Streptomyces hygroscopicus (soil bacteria), found to have anti-T-cell properties and classifies as an anticancer drug from the mammalian target of rapamycin (mTOR) inhibitors. Sirolimus binds with mTOR and causes inhibition of mTOR activity and VEGF‑stimulated endothelial cell proliferation. Topical preparation produced by crushing tablets of sirolimus 1 mcg and mixing in an aqueous base emollient or the solution form of sirolimus has been used with beneficial effects in the treatment of angiofibroma, especially in younger patients. Here we reported a case of a 34-year-old male, a known case of TSC with facial angiofibroma in which the topical 0.1% sirolimus had been used with beneficial effects and clinical outcomes.